Organizational Life Cycle Assessment: A Systematic Review of Experiences, Applications and Lessons Learned - Junior, Jose Hugo L.; Piekarski, Cassiano M.; Santos, Macio G; Francisco, Antonio C. (Journal of Environmental Accounting and Management, 2026)
The main objective of this paper was to analyze the Organizational Life Cycle Assessment (O-LCA) method, discussing its applicability based on papers that presented case studies or discussed the concept. Scientific productions from researchers and organizations were used to discuss advances in the O-LCA scientific approach. The systematic literature review method was performed, using the STARR-LCA (Zumsteg et al, 2012) and PRISMA (Moher et al, 2009) models, in 14 scientific papers indexed in two scientific databases, Scopus and Web of Science, from 2012 to 2020. It was given priority to the case studies that applied the OEF or UNEP / SETAC guides, but some authors approach other methods and practices as well, and some followed the steps of the OEF guidelines, ISO 14072 and O-LCA before the establishment of the methodologies themselves. As the O-LCA method is still recent, there are several understandings about its development. The data from this analysis helps organizations and researchers in understanding the divergences and issues that still need discussion to broaden the methodologies and emphasize their roles in the context of Life Cycle Assessment.